Manuel Llorca-Jaña. The British textile trade in South America in the nineteenth century. Cambridge, Cambridge University Press, 2012, 380 págs., ISBN: 978-1-107-02129-7 - Lamikiz Gorostiaga, Xabier (Investigaciones de Historia Económica, 2019)
Sin resumen